Germline Mutational Analysis of the C19orf62 Gene in African-American Women with Breast Cancer - Zheng, Yonglan (2011)
The past two decades have seen steady progress in the field of breast cancer genetics as we continually increase our understanding of how tumorigenesis results from damaged DNA. While BRCA1 and BRCA2 have taken center stage as indicators for breast cancer risk, we continue to identify other susceptibility genes and genomic regions, ever increasing our comprehension of breast cancer etiology. Through genome-wide association studies (GWAS), the 19p13 locus was found to contribute to breast and ovarian cancer risk. This region harbors a gene called C19orf62 whose protein has been reported to be a pivotal component in DNA damage repair. In the present study, complete sequencing was performed to screen for deleterious mutations in the C19orf62 gene. In our cohort of 110 familial and 144 non-familial African-American breast cancer female patients, we identified thirty-five DNA sequence variants, including four missense variants, which appeared unlikely to be disease-causing. We did not detect deleterious frameshift truncating or nonsense mutations in this cohort. Our findings suggest that germline deleterious mutations in C19orf62 should be rare or absent in familial and non-familial breast cancer women. However, the possibility that mutations in C19orf62 contribute to breast cancer risk warrant further studies in large diverse populations.